2005
DOI: 10.1002/bem.20109
|View full text |Cite
|
Sign up to set email alerts
|

Perception of local DC and AC electric fields in humans

Abstract: The goal of this study was to address some of the factors that contribute to the human ability to detect the presence of weak electric fields generated by direct current (DC) and alternating current (AC) sources. An exposure chamber allowed us to expose a limited surface of the body (forearm and hand) to DC fields of up to 65 kV/m and AC fields up to a maximum of 35 kV/m (frequency 60 Hz). Perception was examined using a staircase procedure and a rating procedure derived from signal detection theory. Sixteen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…Further fixation studies revealed that hair plates at the base of the scape (S-HPs) were crucially required for an animal to avoid an electric field. The influences of electric fields on other slender, elongated structures, such as human hairs have previously been reported (Chapman et al, 2005;Shimizu and Shimizu, 2003;Shimizu and Shimizu, 2004). Our results show that the detection of static electric fields by cockroaches can be attributed to the activation of an established sensory system and not one that has evolved specifically for the purpose.…”
Section: The Detection Of Static Electric Fieldssupporting
confidence: 60%
See 2 more Smart Citations
“…Further fixation studies revealed that hair plates at the base of the scape (S-HPs) were crucially required for an animal to avoid an electric field. The influences of electric fields on other slender, elongated structures, such as human hairs have previously been reported (Chapman et al, 2005;Shimizu and Shimizu, 2003;Shimizu and Shimizu, 2004). Our results show that the detection of static electric fields by cockroaches can be attributed to the activation of an established sensory system and not one that has evolved specifically for the purpose.…”
Section: The Detection Of Static Electric Fieldssupporting
confidence: 60%
“…For example, the wings of Drosophila and bees vibrate when exposed to both static and VLF electric fields (Bindokas et al, 1988;Watson et al, 1997) whereas the antennae of bees and parasitoids appear to be deflected by electric fields (Maw, 1961;Yes'Kov and Sapozhnikov, 1976). It is possible, therefore, that insect appendages are involved in the detection of electric fields, much in the same way that body hairs are believed to contribute to the perception of electric fields by humans (Chapman et al, 2005). Body hairs are deflected by electric fields with the angle of displacement being proportional to the field strength (Shimizu and Shimizu, 2003;Shimizu and Shimizu, 2004) and removal of hairs abolishes our ability to detect such fields (Chapman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field perception experiments provided evidence that detection thresholds for static EF are much lower for whole-body exposure [29, 31] than limb exposure (e.g., arm and forehand) [30, 34]. Because these effects were confirmed by independent investigators, they can be considered as replicated.…”
Section: Resultsmentioning
confidence: 99%
“…or combined with air ions?) for approximately 1 hphysiological/health-related effects:blood parameters; respiration rate; pulse; blood pressure; brightness detection; reaction times; field awareness; muscular steadinessno significant effectalso air ions tested; not clear if peer-reviewed, all subjects were pilotsBlondin et al [29]whole-body( n  = 48)static EF of <10 to 50 kV/m alone or in combination with air ions; 7–11 s per trial (several 100 trials during 1 day)field perceptionmedian perception threshold 45.1 kV/m without ions; high ion densities lowered the median threshold to 36.9 kV/mChapman et al [30]arm( n  = 16)static EF of 30 to 65 kV/m; 7–11 s per trial (several 80 trials during 1 day)field perceptionsubjects did not perceive static EFalso AC EFClairmont et al [31]whole-bodystatic EF of −40 to 40 kV/m alone or combined with different AC EFfield perceptionperception threshold of static EF 10–20 kV/m; simultaneous AC EF lowered the thresholdmain focus was technicalHaupt and Nolfi [35]whole-body( n  = 438)static EF of approx. −16 to 21 kV/m and static MF of 22 μT of a HVDC line for at least 5 yearsphysiological/health-related effects:self-reported health issues (e.g., headache, depression, allergies, illness days)no significant effectcross-sectional epidemiological studyOdagiri-Shimizu and Shimizu [34]human arm ( n  = 10–30 per condition)static EF up to 450 kV/m with variable humidityfield perceptionaverage perception threshold approx.…”
Section: Methodsmentioning
confidence: 99%